Nonalcoholic Fatty Liver Disease in Patients Investigated for Elevated Liver Enzymes - Krikor Kichian; Ross Mclean; Leah M Gramlich; Robert J Bailey; Vincent G Bain (Canadian Journal of Gastroenterology)
Nonalcoholic fatty liver disease (NAFLD) is a common diagnosis among patients referred to gastroenterology and hepatology clinics for the evaluation of elevated liver enzymes. The diagnosis of NAFLD is supported by blood work to exclude other liver diseases, and by ultrasound evidence of fat in the liver in patients without a significant history of alcohol intake. The gold standard, however, is a liver biopsy to show the typical histological features of NAFLD, which are almost identical to those of alcohol-induced liver damage and can range from mild steatosis to cirrhosis. A variety of retrospective series have linked NAFLD to obesity, diabetes, hyperlipidemia, total parenteral nutrition, jejunoileal bypass surgery and certain medications. A subset of patients with NAFLD that had an initial presentation of elevated liver enzymes was studied. Two hundred and two patients were reviewed, of whom 49 met the inclusion criteria including a liver biopsy. Patients were excluded if insufficient data were available, if the patients had a significant history of ethanol intake or if they had other coexisting liver disease. These patients were seen between 1996 and 2000 in gastroenterology and hepatology clinics in two community hospitals and one regional liver transplant centre in Edmonton, Alberta. NAFLD was associated with a spectrum of changes in the liver ranging from mild steatosis to more significant steatosis with inflammation and fibrosis. Cases of NAFLD with steatosis and mixed inflammatory infiltration but lacking ballooning degeneration or fibrosis were prevalent in young (20 to 40 years of age) patients with no other significant medical history except for obesity. NAFLD with biopsies showing significant fibrosis and ballooning cell degeneration was associated with obesity, diabetes and older age. It was concluded that, in this predominantly outpatient setting, age over 40 years and diabetes at any age are risk factors for both nonalcoholic steatohepatitis and nonalcoholic steatohepatitis with cirrhosis. It is therefore recommended that patients with raised liver enzymes and suspected NAFLD be targeted for liver biopsy in their evaluation.